The Influence of Language Environment (Bi'ah Lughawiyah) on the Acquisition of Arabic Speaking Skills (Maharah Kalam) in Ma'had: A Systematic Literature Review - Alfan Zuhdi; Irpan Apandi Batubara; Anugrah Ilahi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to systematically analyze the influence of the language environment (bi'ah lughawiyah) on the effectiveness of Arabic speaking skills (maharah kalam) learning in ma'had-based educational institutions. A Systematic Literature Review (SLR) approach was employed following the PRISMA 2020 protocol to ensure a transparent, reproducible, and rigorous review process. A total of 20 peer-reviewed journal articles published between 2011 and 2025 were selected from DOAJ and SINTA databases after a systematic screening of 200 initial records. Thematic synthesis was conducted to identify patterns, strategies, and outcomes across studies. The findings indicate that both formal environments (classroom instruction, curriculum, textbooks, institutional policies) and informal environments (daily interactions, dormitory activities, muhadharah, Arabic camps, language area systems) significantly contribute to improving students' speaking fluency, accuracy, and confidence. The integration of innovative media, gamification, habitual Arabic communication, and psychological support from teachers and dormitory supervisors effectively reduces speaking anxiety (by up to 78%) and increases learning motivation and class participation (by up to 85%). However, major obstacles persist, including inconsistent use of Arabic outside the classroom, variability in teacher pedagogical and linguistic competence, limited access to technology, and weak supervision of language policies. This study concludes that strengthening the language environment through a participatory, policy-driven, and technology-integrated approach is essential for natural, communicative, and sustainable maharah kalam acquisition in ma'had settings. Theoretical implications extend Krashen's affective filter and input hypotheses to the Islamic boarding school context, while practical implications offer evidence-based guidelines for ma'had leaders, teachers, and policymakers.